Effect of interpregnancy interval on gestational diabetes: a retrospective matched cohort study - Gebremedhin, Amanuel Tesfay; Regan, Annette; Ball, Stephen; Betrán, A.P.; Foo, D.; Gissler, M.; Håberg, S.E.; Malacova, Eva; Marinovich, M. Luke; Pereira, Gavin (2019)
© 2019 The Authors Purpose: To examine the association between interpregnancy interval (IPI) and gestational diabetes using both within-mother and between-mother comparisons. Methods: A retrospective cohort study of 103,909 women who delivered three or more consecutive singleton births (n = 358,046) between 1 January 1980 and 31 December 2015 in Western Australia. The association between IPI and gestational diabetes was estimated using conditional logistic regression, matching pregnancies to the same mother and adjusted for factors that vary within-mother across pregnancies. For comparison with previous studies, we also applied unmatched logistic regression (between-mother analysis). Results: The conventional between-mother analysis resulted in adjusted odds ratios (aOR) of 1.13 (95% CI, 1.06–1.21) for intervals of 24–59 months and 1.51 (95% CI, 1.33–1.70) for intervals of 120 or more months, compared with IPI of 18–23 months. In addition, short IPIs were associated with lower odds of gestational diabetes with (aOR: 0.89; 95% CI, 0.82–0.97) for 6–11 months and (aOR: 0.92; 95% CI, 0.85–0.99) for 12–17-month. In comparison, the adjusted within-mother matched analyses showed no statistically significant association between IPIs and gestational diabetes. All effect estimates were attenuated using the within-mother matched model. Conclusion: Our findings do not support the hypothesis that short IPI (<6 months) increases the risk of gestational diabetes and suggest that observed associations in previous research might be attributable to confounders that vary between mothers.